Hybrid Renewable Energy Systems: Efficiency and Sustainability in Power Plants - Yaat, Ky; Kheng, Sok (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2025)
This study analyzes the efficiency of hybrid renewable energy systems combining solar, wind, biomass, and energy storage to improve power plant reliability and reduce carbon emissions. Simulations using HOMER Pro software reveal system efficiency reaching 55%, with cost reductions to 0.04/kWh. Hybrid systems demonstrate lower carbon emissions than fossil-based technologies, offering environmental and economic benefits. These findings highlight the necessity of advancing energy storage technologies and optimizing resource utilization for clean energy transitions.